2015
DOI: 10.1007/s00345-015-1541-4
|View full text |Cite
|
Sign up to set email alerts
|

The vacuum cleaner effect in minimally invasive percutaneous nephrolitholapaxy

Abstract: This study illustrates and explains the vacuum cleaner effect which has been detected in the development of the Nagele Miniature Nephroscope System used in MIP. It combines the reduced morbidity of smaller kidney puncture diameters with the benefit of quick and complete stone removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 28 publications
0
21
0
2
Order By: Relevance
“…The first description of standard “minimally invasive PCNL” with specialized 12-Fr rigid nephroscope and 15-Fr access sheath came out in 2001. However, according to the authors' note, despite the fact that no hemorrhage has occurred in a group of 19 patients, miniaturized instruments were associated with significant operative time increase with larger stone masses [19], due to the fact that utilization of a smaller sheaths are associated with more difficult stone fragment retrieval and need of additional tools such as disposable retrieval baskets [4]. It was not until Nagele et al [3] in 2008 reported on a “Newly Designed Amplatz Sheath” (Karl Storz) with the vacuum cleaner effect, which was nicely depicted in a study by Nicklas et al [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first description of standard “minimally invasive PCNL” with specialized 12-Fr rigid nephroscope and 15-Fr access sheath came out in 2001. However, according to the authors' note, despite the fact that no hemorrhage has occurred in a group of 19 patients, miniaturized instruments were associated with significant operative time increase with larger stone masses [19], due to the fact that utilization of a smaller sheaths are associated with more difficult stone fragment retrieval and need of additional tools such as disposable retrieval baskets [4]. It was not until Nagele et al [3] in 2008 reported on a “Newly Designed Amplatz Sheath” (Karl Storz) with the vacuum cleaner effect, which was nicely depicted in a study by Nicklas et al [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the authors' note, despite the fact that no hemorrhage has occurred in a group of 19 patients, miniaturized instruments were associated with significant operative time increase with larger stone masses [19], due to the fact that utilization of a smaller sheaths are associated with more difficult stone fragment retrieval and need of additional tools such as disposable retrieval baskets [4]. It was not until Nagele et al [3] in 2008 reported on a “Newly Designed Amplatz Sheath” (Karl Storz) with the vacuum cleaner effect, which was nicely depicted in a study by Nicklas et al [4]. The basis of this effect lies in Bernoulli's principle, according to which an increase in the speed of a fluid in the constriction zone occurs simultaneously with a decrease in pressure [20], also known as ‘pseudocavity’ which is being located at the tip of the nephroscope during mini-PCNL able to extract stone fragments through access sheath without any additional stone extracting devices [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 80‐W holmium laser (Trimedyne, Irvine, CA, USA) was used to break stones. No stone forceps were used to extract fragmented stones, because the endoscopy irrigation pump (Stryker, Kalamazoo, MI, USA) enabled fragments to go out of the body spontaneously through the sheath . After PCNL procedure, flexible ureterorenoscopes were inserted into the PCNL side in an antegrade or a retrograde manner, and active removal of remnant stones was carried our simultaneously, as shown in Figure .…”
Section: Methodsmentioning
confidence: 99%